Applying and optimizing trajectory approach for performance evaluation of AFDX avionics network - Bauer, H.; Scharbarg, J.-L.; Fraboul, C. (2009 IEEE Conference on Emerging Technologies & Factory Automation, 2009)
AFDX (avionics full duplex switched Ethernet) standardized as ARINC 664 is a major upgrade for avionics systems. But network delay analysis is required to evaluate end-to-end delay's upper bounds. The network calculus approach, that has been used to evaluate such end-to-end delay upper bounds for certification purposes, is shortly described. In this paper we present how the trajectory approach can be applied to an AFDX avionics network. Moreover we explain how this approach can be optimized in this context. We show that, on an industrial configuration, it outperforms existing end-to-end delays upper bounds.